Home, Uprooted : Oral Histories of India's Partition - Chawla, Devika (Book collections on Project MUSE., 2014)
The Indian Independence Act of 1947 granted India freedom from British rule, signaling the formal end of the British Raj in the subcontinent. This freedom, though, came at a price: partition, the division of the country into India and Pakistan, and the communal riots that followed. These riots resulted in the deaths of an estimated 1 million Hindus and Muslims and the displacement of about 20 million persons on both sides of the border. This watershed socioeconomic-geopolitical moment cast an enduring shadow on India's relationship with neighboring Pakistan. Presenting a perspective of the mid.